The Effect of Celebrity Endoser's Country of Origin on Consumers Purchase Intention-An Evidence from Consumer in Pakistan - Mudassir, Wardah (2015)
The aim of the present research is to discover the impact that celebrity endorser has on consumers’ purchase intention through a cross-cultural exchange of celebrities in the field of marketing. The strategy of using celebrities to endorse a brand or product has been used by the marketers for decades now. The ultimate popularity of this method can be explained by witnessing the presence of an international celebrity face in every second advertisement seen on television or billboards. Many researchers have written and tested this approach in the western countries. Through contemplating them as a source of origin of the technique, this research aims to provide some academic literature in a country like Pakistan. The thesis begins with an introduction of the topic followed by literature review that sets a foundation of the research by providing an insight to the knowledge already existent by various academicians. The framework that has been proposed on celebrity endorser’s country of origin and its effect on consumers’ purchase intention is base on the existing literature. The research carried out is empirical and the methodology adopted for the research is quantitative in nature. Data has been collected through an online questionnaire survey answered by 150 respondents. The results of this research came up with interesting outcomes, which contradicted to the literature that suggests celebrity endorser’s credibility have potential to enhance consumers’ purchase intention. The impact of the celebrities’ credibility varied among the two selected countries where Pakistani celebrity was rated as a high credible source as compared to the Indian celebrity. However, Indian celebrity endorser showed the maximum potential for creating direct brand equity by increasing consumers’ interest in purchasing the product in comparison to the Pakistani celebrity. The selection of right celebrity endorser is a critical aspect as it affects the consumers’ attitude toward the advertisement, the brand and their purchase intention. Celebrity endorsements vary with respect to different countries and the culture they practice. This research is valuable for the brand managers of domestic and international companies/brands in Pakistan as it highlights that the cross-cultural exchange of celebrities would work in their favor. This is summarized under conclusion and has set a base for future managerial implications.